Effect of PVY infection on photosynthesis of tobacco - GUO Xing-qi; WEN Fu-jiang; ZHU Han-cheng (浙江大学学报. 农业与生命科学版, 2000)
The objective of this study was to evaluate the effect of PVY infection on the photosynthesis of tobacco under relatively steady laboratory conditions. Physiological properties and ultrastructure in leaves of tobacco variety NC89 were observed at different time after inoculation with PVY. The results showed that the content of chlorophyll, net photosynthetic rate (Pn), evaporative rate, stomatal conductance (Gs) and the activity of Hill reaction decreased, while intercellular CO2 concentration (Ci) increased in comparison with that of the healthy plants. The virus infection also resulted in changes in the chloroplast ultrastructure. The ultrastructural analysis of leaves showed that chloroplast structure was destroyed by PVY infection.